What the fair minded observer really thinks about judicial impartiality - Higgins, A; Levy, I (Wiley, 2021)
This article presents the results of an empirical study designed to assess the degree of convergence and divergence between public opinion and the fictional Fair Minded Observer (‘FMO’) used to determine whether a judge ought to be disqualified on the grounds of possible bias. As part of the test for apparent bias, judges have to imagine whether an FMO would see a risk of bias on the part of the judge. Although the courts have never definitively stated whether the FMO is meant to represent an ideal or average member of the public, to the extent that the FMO is partly meant to reflect public perception, the obvious weakness in the test is that no one has tested public attitudes to the risk of judicial bias specifically. In our study, we conducted nationally representative public surveys in both the UK and Australia, asking respondents what they think about different situations of possible bias (N=2064). Our results, in the form of descriptive statistics, indicate that a gap exists between the FMO created by the courts and public opinion in both the UK and Australia. This gap extends across a number of areas thought to give rise to possible bias, including financial interests and relationships and the risk of prejudgement, as well as fact patterns based on leading cases. There are methodological limitations in nationally representative opinion surveys, which make it difficult to measure informed and reasonable public opinion. While further research would be desirable, if the law of bias continues to be partly framed around the need to maintain public confidence in the legal system, law and policy makers will need to take some account of the results of studies such as this one.